Pharmacological Action of Kankasava in Bronchial Asthma Based on Practical Experience: A Review - Sahu, Preeti; Sharma, Karan Prakash; Rajpurohit, Ranweer; Meena, HML; Mutha, Rashmi (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is among the most important systems of Indian medicine, and as we all know, it is a science of life. After much research, observations, experiments, thoughts, trials, and judgements, the ancient sages developed several types of Ayurvedic remedies. Ayurveda provides us with this health expertise. As opposed to many ailments that may be related to contemporary man’s lifestyle, asthma is an old sickness. Bronchial Asthma is caused by a combination of factors. The illness is linked to geographical location, environmental, racial, and behavioral and lifestyle variables. Tamaka Shwasa is a condition described in Ayurvedic literature that, based on clinical signs, is quite similar to bronchial asthma. According to conventional medical science, there is no treatment for asthma. Ayurvedic medicines have the potential to be a viable and successful therapy option for bronchial asthma. Ayurvedic medications are utilized for illness treatment all around the globe, thus people all around the globe may have trust in them based on scientific proof. The current study was a review to determine the effectiveness of Kanakasava on Tamaka Shwasa (bronchial asthma). Kanakasava is a composition that has been used for thousands of years by Ayurvedic physicians to alleviate the symptoms of Tamaka Shwasa.